Selective transport of nutrients via the rhizoids of the water mold Blastocladiella emersonii. - Kropf, D L (1982)
Previous work in this laboratory demonstrated that the rhizoids of Blastocladiella emersonii grow chemotropically toward a source of Pi and thus provided preliminary evidence that, in addition to serving as a holdfast, the rhizoids absorb nutrients. To further examine the role of the rhizoids in nutrient uptake, we devised a technique to introduce a barrier between the rhizoids and the thallus to that these cell compartments could be studied independently. Cells were grown on polycarbonate membrane filters in such a way that all of the thalli were on one side of the filter and essentially all of the rhizoids were on the opposite side. Nutrient uptake into the rhizoids and the thallus was measured by floating the filters bearing cells on radioactive medium so that only one side of the filter contacted the label. Mineral oil was used to block the diffusion of the label through the unfilled pores in the filter. This technique permitted us to establish clearly that the rhizoids absorb all seven of the nutrients tested. In addition, we found that some nutrients, specifically Pi and amino acids, appeared to be preferentially taken up via the rhizoids, whereas K+, Rb+, and Ca2+ entered the thallus and rhizoids equally. Cells grown in the presence of the microtubule synthesis inhibitors nocodazole and carbendazim elaborated only a stunted rhizoid system, so we examined their ability to accumulate the two classes of compounds. As expected, these cells were severely inhibited in Pi and amino acid uptake but retained normal uptake of K+, Rb+, and Ca2+.